The relationship between heavy metals concentrations in soil and plant (Senna auriculata (L.) Roxb.) of the hills and roadsides in Tiruchirappalli, India: Heavy metal concentration in soil and S.auriculata (SAARC Journal of Agriculture, 2022)
The relationship between heavy metal concentrations of soil and plant (Senna auriculata) in the hills and roadsides was studied. Atomic absorption spectroscopy was used for determination of metals such as lead (Pb), chromium (Cr), cadmium (Cd), zinc (Zn), copper (Cu), and iron (Fe) in the soil and plant (leaves and flowers) samples. The results showed that heavy metal concentrations in roadside soil and plant samples were much greater than that in hills. It is evident that concentration of a heavy metal in soil samples are considerably higher (p0.93. Strong positive relationship exists between soil and plant for Cr content, (r≥0.97). Cadmium and Zn contents in leaves and flowers correlated significantly with Cd, and Zn in soil, all r>0.97. The Cu concentration of leaves and flowers shows a positive correlation with Cu content in soil, all r≥0.93. The Fe concentration of both plant leaves and flowers is found significantly and positively correlated with soil Fe, r=0.99. Overall results reveal that all the heavy metals are significantly and positively associated with soil and plant, implying that increasing concentration of heavy metals in soil is likely to increase their concentrations in S. auriculata plant.SAARC J. Agric., 20(1): 121-130 (2022)